The Influence of QRIS Digitalization, Technology and Digitalization Lifestyle, Digital Financial Literacy, and Financial Inclusion On Bank Customers Decision - Mahrizal, Mahrizal; Judijanto, Loso; Indrapraja, Rachmadi; Alfiana; Pujianto, Defi (Jurnal Informasi dan Teknologi, 2023)
This study looks at how consumer decisions are impacted by the digitalization of QRIS, financial literacy, and financial inclusion through lifestyle. The participants in this study are clients of Sharia Bank. Non-probability sampling combined with a purposeful sampling approach was the sample strategy employed in this study. A sample of one hundred participants was used by the researchers. This study included both primary and secondary data. In order to acquire the primary data required by the researchers, the data collection strategy used in this study is the distribution of questionnaires. In this quantitative study, the Partial Least Squares (PLS) method of moderated regression analysis (MRA) and descriptive statistical analysis were employed as data analysis techniques. Based on the test results and discussions that have been described, the following conclusions can be drawn: The digitalization of QRIS has a direct influence on customers' decisions to make transactions using QRIS. Financial literacy has a direct influence on customer decisions. Decisions made by customers are directly impacted by financial inclusion. Decisions about transactions are directly influenced by lifestyle. The digitalization of QRIS does not directly impact lifestyle. Lifestyle is not immediately impacted by financial knowledge. There is no direct correlation between financial inclusion and lifestyle. Lifestyle cannot moderate the relationship between QRIS digitization and consumer decisions, nor does it have an indirect effect. Lifestyle cannot moderate the relationship between financial literacy and client decisions, nor does it have an indirect influence. Lifestyle cannot moderate the relationship between financial inclusion and customers' decisions to transact via QRIS, nor does it have an indirect influence.